2022
DOI: 10.3390/brainsci12020148
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in People with Lewy Body Disorders and Their Care Partners: Association with Mental Health, Relationship Satisfaction, and Care Burden

Abstract: The emergence of cognitive impairment and dementia in people with Lewy body spectrum disorders (LBS) significantly impacts the quality of life of the individual and their care partner. Coping well with the condition may depend, in part, on the degree of psychological resilience or capacity to ‘bounce back’ from adversity. We explored resilience in people with Parkinson’s disease mild cognitive disorder or dementia, or dementia with Lewy bodies, and their care partners, and its relation to outcomes related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 67 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…By using a cross-sectional monocentric exploratory study, Vatter et al investigated resilience in people with PD dementia and their caregivers [ 17 ]. Lower resilience was associated with higher anxiety and lower quality of life in patients with PD dementia.…”
mentioning
confidence: 99%
“…By using a cross-sectional monocentric exploratory study, Vatter et al investigated resilience in people with PD dementia and their caregivers [ 17 ]. Lower resilience was associated with higher anxiety and lower quality of life in patients with PD dementia.…”
mentioning
confidence: 99%
“…Two studies [ 42 , 66 ] each report on two different measures so data for each measure is presented separately in Table 2 , generating a total of 53 psychometric assessments. The majority of the studies focussed on carers ( n = 47), three studies focused on people living with dementia, and one study [ 45 ] focussed on the dyad (people with dementia and their carers). One study [ 48 ] sought to adapt and evaluate the psychometric properties of positive psychology measures (which included a resilience measure, the RS-14) for people living with dementia.…”
Section: Resultsmentioning
confidence: 99%
“…85% 9 n = 116) female; 95% ( n = 129) married; 89% ( n = 122) white British; mean age = 69.4 (SD = 7.62) England (English) Cross sectional design derived from a pilot feasibility study (Face to face interviews and self-completion) None specified Reliability not reported in this study sample Not hypothesis driven: The study reports a large negative correlation between carer resilience and the Zarit Burden scale ( r = -0.53, p < 0.001), and medium and large correlations between carer resilience and five dimensions derived from a factor analysis; social and psychological constraints ( r = -0.40, p < 0.001); personal strain ( r = -0.50, p < 0.001); interference with personal life ( r = -0.38, p < 0.001); concerns about the future (r = -0.34, p < 0.001) and guilt ( r = -0.31, p < 0.001) Vatter et al [ 44 ] (To explore and compare levels of mental health, care burden, and relationship satisfaction among caregiving spouses of people with mild cognitive impairment or dementia in Parkinson disease (PD-MCI or PDD) or dementia with Lewy bodies (DLB) N = 136 spouse/life partner caregivers (same participants as reported in Vatter et al, 2018) England (English) Cross sectional design derived from a pilot feasibility study (Face to face interviews and self-completion) None specified Reliability not reported in this study sample Not hypothesis driven: No differences were found for carer resilience across the three types of dementia Medium negative and large correlations between carer resilience and ZBI ( r = -0.47, p < 0.01); anxiety ( r = -0.59, p < 0.01); depression ( r = -0.54, p < 0.01); relatives stress ( r = -0.50, p < 0.01); relationship strain ( r = -0.33, p < 0.01); role resentment ( r = -0.42, p < 0.01); role anger (r = -0.32, p < 0.01). Positive correlations between carer resilience and mental health ( r = 0.59, p < 0.01); health related quality of life ( r = 0.35, p < 0.01); self-rated health ( r = 0.34, p < .01) Vatter and Leroi [ 45 ] (To explore resilience in people with Parkinson’s disease mild cognitive disorder or dementia, or dementia with Lewy bodies, and their care partners, and its relation to outcomes related to their mental well-being and quality of life) N = 76 dyads ( n = carers and n = 76 people with dementia) Of the participants w...…”
Section: Resultsmentioning
confidence: 99%
“…Psychosocial interventions should focus on enhancement of the positive aspects of caring which could reinforce caregivers' well-being, resilience and reduce the impact of stress and burden. [14][15][16][17] Positive aspects of caregiving for a family member with a progressive neurological disorder can affect adaptation to bereavement in terms of depression and grief. 18 The aim of this mixed methods, exploratory analysis was to explore both caregiver burden and self-described positive experiences of informal caregivers of people with ALS attending two multidisciplinary clinical centres in Dublin and Utrecht.…”
Section: Introductionmentioning
confidence: 99%
“…ALS is a progressive neurodegenerative disorder with death occurring approximately 3–5 years after symptom onset, 13 and it is particularly important to explore the positive as well as the negative aspects associated with caregiving to support caregiver wellbeing. Psychosocial interventions should focus on enhancement of the positive aspects of caring which could reinforce caregivers' well‐being, resilience and reduce the impact of stress and burden 14‐17 . Positive aspects of caregiving for a family member with a progressive neurological disorder can affect adaptation to bereavement in terms of depression and grief 18 …”
Section: Introductionmentioning
confidence: 99%